Global gene expression analysis of Streptococcus agalactiae at exponential growth phase - Silvestre, Inês (2022)
A comparative overview of the global gene expression levels of S. agalactiae reference strain NEM316 at the exponential growth phase was done through RNA-sequencing. The expression levels of 47 genes potentially linked to virulence evidenced that: i) the major nuclease, GBS_RS03720/gbs0661, presented higher mean expression values than the remainder of DNase genes; ii) the genetic pilus island PI-2a genes presented higher mean expression values than PI-1 coding genes; and, iii) three virulence-associated genes ranked among the top-100 most expressed genes (GBS_RS07760, GBS_RS09445 and GBS_RS03485). Among this top-100, genes encoding proteins involved in "Translation, ribosomal structure and biogenesis" represented 46%. Curiously, genes with no assigned function were grouped in the category of highly expressed genes. As very little is known about the molecular mechanisms behind the release of DNases, preliminary assays were developed to understand whether direct DNA exposure would affect gene expression at the exponential growth phase. No differentially expressed genes were detected, indicating that follow-up studies are needed to disclose the complex molecular pathways (and stimuli) triggering the release of DNases. In general, our insights on the global expression levels of NEM316 at exponential growth phase with and without DNA exposure should open novel research lines to decipher S. agalactiae puzzling adaptation and virulence mechanisms, such as DNase production.